Development of Educandy-Based Interactive Poster Learning Media in Elementary School for Natural and Social Sciences Lessons - Siti Arinda Widaningsih; Astri Sutisnawati; Din Azwar Uswatun (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2023)
Along with the development of the times, changes always occur, including in the world of education. One of them is the education system in Indonesia, namely, the curriculum, the curriculum in Indonesia always changes with the times. Just as the Minister of Education and Culture issued a new curriculum, namely the independent curriculum, in this independent curriculum there were two important tools that were formulated, namely the independent curriculum and the independent platform. The Merdeka curriculum is designed in a simple and in-depth manner, while the Merdeka platform utilizes existing technology. as was the case during an interview at one of the public schools, media facilities and feelings were already available but had not been utilized optimally, therefore the researchers worked together to make educational media interactive posters based on educandy to facilitate students in the learning process. This study aims to produce and describe the feasibility of educandy-based interactive posters in science learning based on material, media and practitioner validation and to find out how students respond to educandy-based interactive posters when used in research. This research method uses the ADDIE development model. This study produced educandy-based interactive digital posters and obtained 97% results from material experts, media experts and practitioner experts while student responses obtained very good responses as evidenced by obtaining 93% results in the very good category. Data collection techniques and data analysis, namely, interviews, questionnaires and expert validation while qualitative and quantitative data analysis.